The Fe/Ni ratio in ionized nebulae: clues on dust depletion patterns. Issue 4 (13th January 2016) - Delgado-Inglada, G.; Mesa-Delgado, A.; García-Rojas, J.; Rodríguez, M.; Esteban, C.
Abstract: We perform a homogeneous analysis of the Fe/Ni abundance ratio in eight Galactic planetary nebulae and three Galactic H ii regions that include the Orion nebula, where we study four nebular zones and one shocked region. We use [Fe ii ], [Fe iii ], and [Ni iii ] lines, and ionization correction factors (ICFs) that account for the unobserved ions. We derive an ICF for nickel from an extensive grid of photoionization models. We compare our results with those derived by other authors for 16 neutral clouds in the solar neighbourhood with available Fe/Ni ratios in the literature. We find an excellent agreement between the ionized nebulae and the diffuse clouds, with both types of regions showing a clear correlation between the Fe/Ni ratios and the iron and nickel depletion factors. The trend shows that the objects with a relatively low depletion have near solar Fe/Ni ratios whereas at higher depletions the Fe/Ni ratio increases with the depletion. Our results confirm that, compared to iron atoms, nickel ones are more efficiently stuck to the dust grains in ambients where dust formation or growth have been more efficient.